Айдентика, як інструмент психологічного впливу - Федосенко, Я. С. (ХНУРЕ, 2025)
The paper examines the phenomenon of identity as a complex tool of psychological influence. The theoretical foundations are analyzed, in particular the theories of social identity and self-categorization, as well as practical application in marketing, media and the social sphere. Special attention is paid to the ethical aspects of the use of identity and the need for a balance between commercial interests and social responsibility. The role of identity in the formation of a positive image and influence on the audience in conditions of high competition.
Keywords: айдентика; інструмент психологічного впливу